2014
DOI: 10.1007/s12020-014-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive glycemic control in ocular complications in patients with type 2 diabetes: a meta-analysis of randomized clinical trials

Abstract: Whether intensive glycemic control can reduce incidence of diabetic retinopathy or other diabetes-associated ocular complications remains undefined. In this meta-analysis, we assessed the effects of intensive versus conventional glycemic control in ocular complications in patients with type 2 diabetes. A systematic literature search of PubMed, Web of Knowledge, and Scopus (until December 12, 2013) was conducted. Randomized controlled trials which compared intensive glycemic control with conventional glycemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
1
24
0
3
Order By: Relevance
“…The RCTs focused on the effects of glycaemic control, hypertension, and/or aspirin use on CS. No significant association (odds ratio [OR] and 95% confidence intervals [CI] 0.88 (0.76‐1.03) was found in a prior meta‐analysis of the effect of intensive glycaemic control on CS . As there were not sufficient other RCTs with the same risk factors (two on hypertension, one on dyslipidaemia, and one on aspirin), no updated meta‐analysis was conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCTs focused on the effects of glycaemic control, hypertension, and/or aspirin use on CS. No significant association (odds ratio [OR] and 95% confidence intervals [CI] 0.88 (0.76‐1.03) was found in a prior meta‐analysis of the effect of intensive glycaemic control on CS . As there were not sufficient other RCTs with the same risk factors (two on hypertension, one on dyslipidaemia, and one on aspirin), no updated meta‐analysis was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the negative studies included participants with newly diagnosed diabetes and thus a relatively short duration of glycaemic exposure. These RCTs were included in a meta‐analysis by Zhang et al from which it was concluded that, compared with conventional diabetes treatment, intensive management did not significantly attenuate cataract development (OR 0.88 [95%CI: 0.76‐1.03]) …”
Section: Discussionmentioning
confidence: 99%
“…914 The body of evidence, previously summarized in meta-analyses of large RCTs, appears to confirm this impression (Table S1). 1525 This evidence has contributed to a consensus reflected in universal guideline recommendations, quality improvement efforts, and clinical decisions all promoting tight glycemic control (HbA1c <6.5 or 7.0%). 2628 The same evidence, however, has led some critics to question this consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Each 1% reduction in HbA1c reduces any endpoint related to diabetes by 21% [41]. There is level 1 evidence (grade A recommendation) for intensive glycemic control for reducing the progression of DR [42, 43]. In the DCCT study of patients with type 1 diabetes, intensive therapy to maintain normal glucose blood levels and HbA1c < 6.5% reduced the risk for the development of retinopathy by 76% and the progression of retinopathy by 54% [4].…”
Section: Treatment Of Drmentioning
confidence: 99%